Tobacco Taxation in Croatia – Comparison Within EU Context - Barać, Željana Aljinović; Markota, Ljerka; Rogošić, Andrijana; Vuko, Tina (European Scientific Journal, ESJ, 2018)
In order to instigate the smoking cessation various international initiatives highly recommend increased tobacco taxation as significant tool of tobacco control. This study examines tobacco taxation and its effects in Croatia comparing to the other EU Member States. The analysis is focused on taxation of cigarettes because the other tobacco products (like cigars, cigarillos, fine cut smoking tobacco) have low market share. The other reason for exclusion of the other tobacco product is lack of taxation harmonisation since Member States can choose between a specific duty or an ad valorem duty, or may apply a mixture of the two which prevents a valid comparability of taxation effects between EU countries. Research results show that there are great differences in amount of specific excise duty between EU countries. The other component of excise tax, ad valorem, varies between 1% (in Denmark and Sweden) and 52% of tax included retail selling price (in Finland). When total tax burden is considered, it was found that it varies from 69.39% of weighted average cigarettes price in Luxembourg to 89.57% in Estonia. The retail price of cigarettes in Croatia is among the lowest in EU despite the total tax burden of 81.1%. Tobacco control activities in Croatia are showing progress but needing more effort in order to induce serious smoking cessation.